Compendium of the Health and Wellness Coaching Literature - Sforzo, Gary A. (Am J Lifestyle Med, 2017)
Health and wellness coaching (HWC) for lifestyle behavior change is emerging as a practice, role, and profession, in diverse health care, employee wellness, and community settings. Health care professionals apply HWC as a behavior change methodology for the prevention and treatment of diabetes, hypertension, hyperlipidemia, heart disease, cancer, and other chronic disorders. The purpose of this systematic review was to provide a comprehensive and organized compendium of HWC literature. To date, extant HWC literature remains scattered with no meaningful summary accessible. Lack of comprehensive summary stems from lack of consensus on HWC definition and standards. We applied a recently proposed, standardized definition of HWC to determine compendium inclusion criteria for peer-reviewed, data-based literature from relevant search engines (ie, PubMed, PsychInfo, and CINAHL). A systematic review process was executed and ultimately yielded 219 articles meeting HWC inclusion criteria. Of these, 150 were data-based and the remainder were expert opinion or review-style articles. A summary of results generally reveals HWC as a promising intervention for chronic diseases though further research is needed in most categories. The resulting HWC compendium organizes and describes the quantity and quality of available literature for the use and benefit of HWC practitioners and researchers.